Superior Mesenteric Artery Syndrome: A Case Report - Dhungel, K; Ansari, S; Ahmad, K; Sah, PL; Gupta, MK; Adhikary, S; Rauniyar, RK (Nepal Journal of Medical Sciences, 2013)
Superior mesenteric artery syndrome (SMAS) is a rare condition caused by compression of the third portion of the duodenum between the superior mesenteric artery (SMA) and the aorta, causing symptoms of duodenal outflow obstruction. We report a case of SMAS in a young emaciated female with well-documented diagnostic imaging findings. Nepal Journal of Medical Sciences | Volume 02 | Number 01 | Jan-Jun 2013 | Page 73-76 DOI: http://dx.doi.org/10.3126/njms.v2i1.7657